P229 Comparison of the characteristics of segmental mucosal microbiome according to the extent of inflammation in ulcerative colitis. (30th January 2023) - Shin, J; Kim, S Y; Kwon, D; Cha, B; Kong, S M; Kim, J S; Kwon, K S; Kim, H
Abstract: Background: Ulcerative colitis (UC) is a chronic characterized by recurrent remission and relapse and is a subtype of inflammatory bowel disease. The gut microbiome is one of the major factors in the pathogenesis and exacerbation of UC. Whether there is a difference in the mucosal microbiome profile for each segment of the colon according to the extent of inflammation in UC remains an uninvestigated field. Therefore, we investigated the differences in the mucosal microbiome according to colonic segments in patients with proctitis (P) vs Lt side colitis (L) vs remission (R). Methods: A total of 28 UC patients who underwent endoscopic evaluation between March 2022 and October 2022 were finally enrolled. The patients were allocated by disease extent to P (n=18, 64.3%) L (n=4, 14.3%), and R (n=6, 21.4%) groups. The microbiomes of the cecum, descending colon, and rectum was evaluated. Total genomic DNA was extracted from the samples, and the character of the microbiome was determined by sequencing the V3-V4 region of the 16s rRNA gene (Miseq). Results: We found that the relative abundance of the rectum and descending colon were increased compared to the cecum in P and L. In segments with active inflammation, Capilobacterota and fusobacteriota phyla were increased and Proteobacteria decreased compared to the cecum. However, in the R group, the relative abundance was not significantly different according to segments.In beta diversity, the microbiome composition was different depending on the segment in the P group. In the L group, the microbiome composition of the rectum and descending colon were similar but separate from the cecum. In the R group, there was no difference in beta diversity by segments. Conclusion: In summary, biopsy microbiome in inflammation and suboptimal remission differs from remission. Assessment of segmental biopsy microbiome may be provided clinical perspicacity into UC disease progression and predict the extension of inflammation.